Communicating the Results of Capacity-Building Initiatives More Effectively: Nigeria Customs Service (NCS) Experience and Lessons Learned - Abdullahi Aliyu Maiwada (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2026)
Capacity building has become a central pillar of institutional reform in public sector organisations, particularly in customs administrations that operate at the intersection of trade facilitation, national security, and revenue generation. However, the effectiveness of such initiatives depends not only on technical reforms but also on the ability of institutions to communicate their outcomes to internal and external stakeholders. This paper examines the strategic communication framework adopted by the Nigeria Customs Service (NCS) in communicating the results of its capacity-building initiatives. Based on institutional reforms implemented in alignment with the Nigeria Customs Service Act of 2023, the paper analyses communication practices related to institutional modernisation, human resource development, and stakeholder engagement. Using empirical examples such as the Time Release Study (TRS), Advance Ruling system, Authorised Economic Operator (AEO) programme, and the B’Odogwu indigenous customs management system, the paper demonstrates how communication strategies transformed technical reforms into measurable institutional credibility and stakeholder trust. The paper situates the NCS experience within broader theoretical discussions on strategic communication, public sector transparency, and trade facilitation governance. The paper argues that communication that emphasises transparency, evidence-based messaging, and stakeholder participation can significantly improve compliance behaviour, institutional legitimacy, and policy outcomes. The paper concludes that communication should be integrated into the design of capacity-building initiatives from the outset, rather than treated as a post-implementation publicity exercise.